2018
DOI: 10.3389/fphys.2018.01151
|View full text |Cite
|
Sign up to set email alerts
|

The Fibrotic Substrate in Persistent Atrial Fibrillation Patients: Comparison Between Predictions From Computational Modeling and Measurements From Focal Impulse and Rotor Mapping

Abstract: Focal impulse and rotor mapping (FIRM) involves intracardiac detection and catheter ablation of re-entrant drivers (RDs), some of which may contribute to arrhythmia perpetuation in persistent atrial fibrillation (PsAF). Patient-specific computational models derived from late gadolinium-enhanced magnetic resonance imaging (LGE-MRI) has the potential to non-invasively identify all areas of the fibrotic substrate where RDs could potentially be sustained, including locations where RDs may not manifest during mappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
(82 reference statements)
0
30
0
Order By: Relevance
“…These computational model predictions have been validated by a recent clinical study that linked the patient-specific LGE areas with locations of RDs recoded using electrocardiography [18]. Moreover, recent computational modelling studies by Boyle et al [19,20] have illustrated correlations between the locations of RDs predicted by patient-specific atrial models and the respective locations found with electrocardiographic imaging (ECGI) and focal impulse rotor modulation (FIRM). In addition to shedding light into the role of fibrosis in the RD dynamics, these studies pave the way to the identification of patient-specific RDs locations from image-based 3D atrial models.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…These computational model predictions have been validated by a recent clinical study that linked the patient-specific LGE areas with locations of RDs recoded using electrocardiography [18]. Moreover, recent computational modelling studies by Boyle et al [19,20] have illustrated correlations between the locations of RDs predicted by patient-specific atrial models and the respective locations found with electrocardiographic imaging (ECGI) and focal impulse rotor modulation (FIRM). In addition to shedding light into the role of fibrosis in the RD dynamics, these studies pave the way to the identification of patient-specific RDs locations from image-based 3D atrial models.…”
Section: Introductionmentioning
confidence: 83%
“…To facilitate future clinical application, it needs to be further developed and clinically validated using EAM techniques such as FIRM or ECGI, which allow for identifying patient-specific RD locations. Indeed, these tools have been used by previous computational studies investigating RD locations by Boyle et al [19,20] to validate their findings and show a fair correlation between model predictions and clinical findings. Moreover, our workflow can be extended to incorporate further patient-specific details, such as atrial fibre orientation and electrophysiological heterogeneity.…”
Section: Plos Computational Biologymentioning
confidence: 96%
“…These changes represented the effect of elevated transforming growth factor-β1, a key component of the fibrogenic signaling pathway. As in previous studies [5,15,16], tissue-scale effects of interstitial fibrosis and gap junction remodeling were represented by reducing overall conductivity and exaggerating the anisotropy ratio (σL:σT) from 5:1 to 8:1 (σL = 0.17708 S m −1 ; σT = 0.022135 S m −1 ).…”
Section: Modeling Of Atrial Electrophysiology In Fibrotic and Non-fibmentioning
confidence: 79%
“…Diffusion‐tensor MRI has been demonstrated for imaging of fiber orientation in both the atria and ventricles . Delayed enhancement MRI and CT can be used for myocardial infarction and fibrosis imaging, which is useful for making accurate diagnoses, predicting outcomes after therapy and treatment planning. MRI and CT have also been used to image adipose in cardiac tissue .…”
Section: Introductionmentioning
confidence: 99%